2012
DOI: 10.1136/tobaccocontrol-2012-050479
|View full text |Cite
|
Sign up to set email alerts
|

Menthol use among smokers with psychological distress: findings from the 2008 and 2009 National Survey on Drug Use and Health

Abstract: Objective The Food and Drug Administration is considering regulation of menthol cigarettes. While persons with mental distress are known to smoke cigarettes at high rates, little is known about their use of menthol. The authors examined the association of psychological distress and menthol use in a national sample of adult smokers. Methods Data were from the 2008 and 2009 National Survey on Drug Use and Health. Past month smokers (N=24 157) were categorised for menthol or non-menthol use. Psychological distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…The 2014 review included 17 publications 28,32,34,37,38,43,73,76,78,79,81,93,[103][104][105][106][107] with a menthol comparison and dozens of analyses, with most of the studies and analyses that examined TTFC reporting no statistically significant difference between menthol and nonmenthol smokers. 28,34,37,43,78,79,81,93,104,106,107 Some studies reported mixed findings (both no difference and shorter/longer) within the same study). 73,105 This review includes results from 19 publications with original data and a recent meta-analysis.…”
Section: Smoking Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…The 2014 review included 17 publications 28,32,34,37,38,43,73,76,78,79,81,93,[103][104][105][106][107] with a menthol comparison and dozens of analyses, with most of the studies and analyses that examined TTFC reporting no statistically significant difference between menthol and nonmenthol smokers. 28,34,37,43,78,79,81,93,104,106,107 Some studies reported mixed findings (both no difference and shorter/longer) within the same study). 73,105 This review includes results from 19 publications with original data and a recent meta-analysis.…”
Section: Smoking Frequencymentioning
confidence: 99%
“…6,36,44,46,49,50,51,62,67,75,84,86,98,102,[108][109][110][111][112] Many of the newly identified analyses report no difference in TTFC among menthol and nonmenthol smokers overall and in a number of subgroups. 36,46,49,50,62,86,98,102,[108][109][110] Studies supporting that menthol smokers have the same or later TTFC as nonmenthol smokers include numerous publications from large or representative studies with adjusted results 6,36,44,49,67,79,107,109,110 and unadjusted results from other large or representative surveys. 73,87,89,91,93,96 Some publications have reported discordant TTFC results (i.e., no difference and longer or shorter TTFC).…”
Section: Smoking Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling and soothing sensation of menthol cigarette smoking, which masks the harshness of inhaled cigarette smoke [14, 15], increases the rewarding and sensory properties of menthol smoking beyond those of nicotine alone and may be particularly appealing to individuals with substance use or mental health problems. Both Hickman et al 2014 and Young-Wolff and colleagues (2015) found an elevated prevalence of menthol cigarette smoking among individuals with psychological distress [16, 17]; while Cohn et al 2016 found higher rates of depression and anxiety in a national sample of young adult menthol tobacco users, relative to non-menthol tobacco users [18]. Further, qualitative work suggests that menthol cigarettes may heighten drug-related high and help to sustain euphoric mood [19].…”
Section: Introductionmentioning
confidence: 99%
“…Kiviniemi et al 2010 found that psychological distress was correlated with higher smoking prevalence and increased odds of poor cessation outcomes among White, but not Black smokers [25]. However, menthol cigarettes are disproportionately used by Black smokers [26], and research shows elevated rates of psychological distress among menthol cigarette smokers relative to non-menthol smokers [16, 17]. However, there are no studies of differences across Black and White menthol and non-menthol smokers on mental health factors.…”
Section: Introductionmentioning
confidence: 99%